An insulin-like peptide specific for a cockroach male reproductive gland - Viviana Pagone; David Pujal; José Luis Maestro (PLoS ONE, 2025)
The insulin-IGF-signalling (IIS) pathway plays crucial roles in animal physiology. In insects, this pathway uses multiple ligands, insulin-like peptides (ILPs), and a smaller number of insulin receptors (InRs). Consequently, much of the regulation of IIS pathway activity is driven by the expression of ILPs, its timing, tissue specific expression, and mode of action: endocrine, paracrine, or autocrine. In the adult male of the cockroach Blattella germanica, tissue expression and the regulation in relation to food restriction of the ILPs BgILP1–7 is similar to that observed in females. However, we identified the expression of BgILP8, an ILP absent in females, in the conglobate gland of males and only in this organ. BgILP8 expression in the conglobate gland is high during the initial days of adulthood and is reduced under starvation. The conglobate gland is a male sexual gland specific to cockroaches, involved in spermatophore formation. It consists of branches of coiled tubules that merge into a main collecting tubule, which opens into the ejaculatory duct. Each tubule is lined with a layer of secretory cells, each of them traversed by small ductules made of cuticle and actin fibers, through which the secretions are released. Decreasing BgILP8 levels through RNAi resulted in a reduction in the size of secretory cells, although the total protein extracted remained unaffected. A comparison of the transcriptomes of control and BgILP8-depleted glands revealed only small differences. Further, comparing genes expressed in the conglobate gland to those expressed in adult females provided a list of putative conglobate gland-specific genes. Our results suggest that BgILP8 plays a role in the development of the conglobate gland. However, a potential function in other male organs or its possible transfer to the female in the copulation cannot be ruled out.